Modernism and the queer: Djuna Barnes/Gertrude Stein - Shin, E (2013)
Djuna Barnes and Gertrude Stein may appear unrelated to one another at first glance. We have an impoverished upstate New Yorker versus relatively comfortable Californian, bisexual romantic nomad versus lesbian monogamist, nihilist versus life-affirming enthusiast, and agnostic-atheist versus secular Jew. When they are referenced together (which happens rarely), it is usually in the context of their Parisian exploits. But a closer look reveals more vital affinities. Both writers remain problematically situated in the modernist canon. Both were inspired by visual art. Both struggled to get published during their lifetimes. Both disassociated themselves from mainstream feminist movements, preferring subtler, more idiosyncratic ways of questioning the status quo. Both held a sustained interest in the queer and, as this dissertation seeks to demonstrate, imagined that theme in original ways—Barnes, through loss; Stein, through phenomenology. Writing out of the spirit of Christian martyrdom, Barnes revels in queer suffering and its transfiguring potential: queers extravagantly lose (themselves), fail, and suffer, yet such ordeals aren’t without value. The first half of my dissertation, thus, appraises Barnes’ “queer negativity” in general before pondering how its masochistic energies push against those authorities that would negate the queer. Chapter One analyzes Barnes’ mythical-seeming transgendered figures who encounter profound failure, despite the imaginative freedom emanating from their ahistorical surroundings. Barnes’ sense of queer failure intensifies in Chapter Two, where same-sex desire invokes the abject by symbolically collapsing psychic boundaries between lovers and refusing reproductive futurity. Both chapters contextualize the moral inversion that becomes the focus of Chapter Three: how does such nihilism tragically ennoble the queer and endow it with insurgent impulses? Without taking a self-consciously queer activist stance, Barnes draws on what Gilles Deleuze would later enunciate as an inverted affect regime: the power of punishment to enforce repressive sexual regulations through pain and hence to bridle perversion becomes inverted when punishment opens the portal to pleasure, when pleasure relocates to sites of perversion. If Barnes writes as a romantic martyr, Stein looks at the queer through a phenomenologist’s eyes. The reciprocity between social conditioning and consciousness, in particular, remains an urgent concern throughout her career. To be “queer,” one often breaks away from a lifetime of habituated orientations toward sex and gender. But queerness cannot wholly bracket the norms that have been left behind. It exists in relation to what it queers. Foregrounding this discussion, Chapter Four examines how Stein’s modernism, phenomenology, and queer criticism intersect. Chapter Five investigates how “Miss Furr and Miss Skeene,” “Many Many Women,” and The Making of Americans reorient us from the “straight” and narrow. Yet this reorientation remains partial. Not all heteronormative biases can be shed, as is evident in The Making of Americans’ classist undertones running through its “singular” queer vision. The sixth chapter further tests the limits of reorientation as such. Ida’s Ida desperately wants to live a queer life, but discovers that she cannot if she approaches queerness as a radically separatist ideal. A solipsistic universe where she can entirely withdraw from society through sleep, silence, or soliloquy remains a fantasy. Ida’s internal conflict, in turn, mirrors Stein’s struggle to enact aesthetic modes that prove just as impossible to practice, being devoted to eliminating memory, emotions, personal identity, and social awareness.